The impact of physical activity on mental health of students in the context of remote learning - Gajda-Bathelt, Monika; Antczak, Tomasz; Dąbek, Monika; Jania, Katarzyna; Perlicka, Zuzanna; Smolińska, Karolina; Sadkowska, Paulina; Kulczycka, Julia; Popow, Weronika; Ciołkosz, Michał (Quality in Sport, 2025)
The COVID-19 pandemic led to an unexpected transition to remote learning, profoundly altering students’ daily routines. Studies report significant declines in physical activity levels during periods of online education. At the same time, elevated levels of anxiety, depression, and stress have been documented among students learning remotely. Evidence indicates that engagement in regular exercise provides mental health benefits: for example, students who engage in physical activity experience significantly reduced anxiety and depression compared to those who do not. In this review, we summarize findings from recent studies, specifically emphasizing how remote learning has led to decreased physical activity and deteriorated psychosocial outcomes. We highlight how physical activity interventions can mitigate stress, anxiety, and depression in student populations. This paper underscores the importance of promoting exercise during periods of online education to support students’ mental well-being.